CONCEPTUAL BASIS FOR THE FORMATION OF THE AGRICULTURAL LAND MARKET PURPOSES (International Journal of Innovative Technologies in Economy, 2018)
In this paper, the conceptual model that describes a wide range of phenomena and processes that will begin in Ukraine's economy after the abolition of the moratorium on land sales. Based on this model, a number of basic conclusions.